Challenges and Strategies in Teaching English as a Second Language (ESL) in Multilingual Classrooms - Anna Olsen; Mette Hansen (International Journal of Multilingual Education and Applied Linguistics, 2024)
This study investigates the challenges faced by educators teaching English as a Second Language (ESL) in multilingual classrooms. By analyzing classroom dynamics, language barriers, and teaching strategies, the research identifies key issues such as student motivation, varying proficiency levels, and cultural diversity. The article proposes several strategies, including differentiated instruction, collaborative learning, and the integration of technology, to address these challenges and enhance ESL learning outcomes.